Maqasid Al-Shari’ah and Legal Pluralism: Normative Analysis of The Principle of Justice in A Multicultural Society - Azizah, Noor Syifa Amaliah; Shalihah, Shalihah (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
In the context of a multicultural society, legal pluralism is an inevitable reality, especially in countries that accommodate various legal systems such as state, customary, and religious laws. One of the main challenges is how Islamic law (sharia) can contribute to justice without creating exclusivity or dominance over other groups. This paper explores the relationship between sharia and legal pluralism, focusing on the question of whether sharia can operate in harmony with the principles of inclusive justice. Through a normative approach, this paper analyzes various examples of sharia implementation in Indonesia, which coexist with other legal systems. The findings indicate that by utilizing the maqasid al-shari‘ah approach which emphasizes the fundamental objectives of Islamic law such as justice, public welfare (maṣlaḥah), and the protection of human rights maqasid al-shari‘ah can play a constructive role in promoting an inclusive legal system. This paper also underscores the necessity for a context-sensitive reform of Islamic law, methodological renewal in fiqh, and the strengthening of dialogue between different legal systems. In this regard, the role of the state as a mediator and the constitution as a normative foundation are vital for ensuring that religious values, human rights, and social justice can coexist in a harmonious manner.